Transcriptomic and Physiological Analysis Reveals Genes Associated with Drought Stress Responses in Populus alba × Populus glandulosa - Tae-Lim Kim; Hyemin Lim; Michael Immanuel Jesse Denison; Changyoung Oh (Plants, 2023)
Drought stress affects plant productivity by altering plant responses at the morphological, physiological, and molecular levels. In this study, we identified physiological and genetic responses in Populus alba × Populus glandulosa hybrid clones 72-30 and 72-31 after 12 days of exposure to drought treatment. After 12 days of drought treatment, glucose, fructose, and sucrose levels were significantly increased in clone 72-30 under drought stress. The Fv/Fo and Fv/Fm values in both clones also decreased under drought stress. The changes in proline, malondialdehyde, and H2O2 levels were significant and more pronounced in clone 72-30 than in clone 72-31. The activities of antioxidant-related enzymes, such as catalase and ascorbate peroxidase, were significantly higher in the 72-31 clone. To identify drought-related genes, we conducted a transcriptomic analysis in P. alba × P. glandulosa leaves exposed to drought stress. We found 883 up-regulated and 305 down-regulated genes in the 72-30 clone and 279 and 303 in the 72-31 clone, respectively. These differentially expressed genes were mainly in synthetic pathways related to proline, abscisic acid, and antioxidants. Overall, clone 72-31 showed better drought tolerance than clone 72-30 under drought stress, and genetic changes also showed different patterns.